Morfologia da placenta a termo e da interface materno-fetal da jumenta pêga - de Toledo, Carmen Zilda Pereira [UNESP]; Girardi, Annita Morais [UNESP]; Toniollo, Gilson Hélio [UNESP]; Orlandi, Cássia Maria Barroso; Machado, Marcia Rita Fernandes [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2015)
This study describes the placental morphology and fetal-maternal interface regarding macroscopic and microscopic aspects from Pêga Jennies at end of pregnancy. Eleven placentas were evaluated after delivery, and four fragments from each placenta were taken in duplicate corresponding to the pregnant uterine horn and non-pregnant horn. Fragments from fetal-maternal interface were obtained from one Jennie at C- section. All fragments were submitted to light microscopy and scanning electron microscopy. Regarding the macroscopic aspect of the placenta, microcotyledons were observed at the endometrial interface, characterized by the diffuse aspect of the placenta. Light microscopy revealed villous type chorion at the chorioallantoic membrane, which were organized in agglomeration villi, presenting a connective tissue stroma and trophoblastic cells. At the fetal-maternal interface, micro placentation, which were composed by inter digitations of agglomeration of villi, limited by maternal crypts, circled by arcades, composed by a fetal trophoblast and an internal portion. In addition, endometrial glands opening were observed. Scanning electron microscopy revealed that the chorioallantoic membranes were covered by villi agglomerations. At the top of those fetal villi we observed cell protrusions from trophoblast cells, which carried debris from maternal tissues. A transversal section from the fetal- maternal interface represented an intricate villi interdigitation with thin maternal caruncle structures, which consist in micro placentation. Macro and microscopic aspects of Jennies’ placenta, as well as the fetal- maternal interface presented similarities with the observed in mares.
Morphology of pêga jennies term placenta and its fetal-maternal interface
Keywords: Fetal-maternal interaction; Jenny; Placenta